On Smooth Families of Diffeomorphic Manifolds and Their Distribution Function (Journal of Mathematical Study, 2024)
We present a formula for the third derivative of the distribution function of aregular function on a domain of $\mathbb{R}^{n+1},$ and a further discussion of the extra assumptionthat the function is harmonic. The present work builds on [3, 5].
Keywords: Level set; third variation.